ADDA and ADADA systems based on triphenylamine as molecular donors for organic photovoltaics. Issue 31 (29th July 2015) - Diac, Andreea; Demeter, Dora; Jungsuttiwong, Siriporn; Grosu, Ion; Roncali, Jean
Graphical abstract: Abstract: Three molecular donor (D) acceptor (A) systems of structure A–D–A–D–A as well as an A–D–D–A compound have been synthesized by spatial extension of reference D–A system containing a triphenylamine donor block (5 ). UV–Vis absorption spectroscopy, cyclic voltammetry and theoretical calculations show that the presence of a median acceptor group has limited effect on the internal charge transfer while direct dimerization leads to an increase of the effective conjugation length. A cursory evaluation of the new compounds as donor material in bilayer solar cells using fullerene C60 as the acceptor material shows that the presence of a median acceptor has deleterious effect on conversion efficiency while the simple dimerization of the molecule leads to a substantial improvement of the short-circuit current density and efficiency.